(untitled) (REMUNOM, 2024)
Through secondary metabolism, plants are capable of producing substances that act to protect themselves and can have different biological activities. Among the botanical families studied by the scientific community, the Piperaceae family stands out, which houses the species Peperomia pellucida. This article aimed to evaluate the yield, phytochemical profile and allelopathic of the crude extract of Peperomia pellucida L. Kunth leaves collected in Itacoatiara. Phytochemical analysis was carried out using chromatic tests. The allelopathic activity was carried out in laboratory 109 of the Federal University of Amazonas, extract concentrations of 5%, 10%, 15% and 20% were used on lettuce and gherkin seeds. The chemical compounds characterized were: Flavonoids, Flavones Terpenes, Tannins, Alkaloids, Saponins and Alkaloids. The species tested has allelopathic potential an inhibitor of seed germination through allelopathy.